High Physical Activity Level and the Long-Term Risk of Atrial Fibrillation in Two Swedish Cohorts - Per Wändell; Malin Enarsson; Tobias Feldreich; Lars Lind; Johan Ärnlöv; Axel Carl Carlsson (Geriatrics, 2025)
Background: Associations between high physical activity (PA) levels and incident atrial fibrillation (AF) is found in some earlier studies. We aim to study the association between levels of PA and AF in two cohorts. Methods: We used data from the Uppsala Longitudinal Study of Adult Men (ULSAM) study, initiated in 1970, included men aged 50 years, with 2202 included in the study. Examinations were reiterated three times, with follow-up after in median 33 years, with 3.8–6.0% on the highest PA level. We also used data from the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS; with women 50%); mean age 70 years, baseline 2001–2004, median follow-up 15 years, with 961 included in the study, with 4.8% on the highest PA level. Cox regression analysis with hazard ratios (HRs) was used to study association between PA levels and incident AF, adjusted for CV risk factors: systolic blood pressure, LDL- and HDL-cholesterol, BMI, diabetes, and smoking. Results: Totally, in ULSAM 504 men during 59,958 person-years at risk, and in PIVUS 204 individuals during a follow-up of 11,293 person-years experienced an AF. Neither in ULSAM, PIVUS, nor in the meta-analysis of both cohorts, individuals with the highest PA level showed an increased AF risk, compared to individuals with lowest level of PA. Conclusions: The benefits of PA in community dwelling individuals for its benefits to mental, metabolic, and cardiovascular health should guide public recommendations, rather than a possible risk of AF. Lay Summary: We studied the risk of incident atrial fibrillation at various levels of physical activity in two cohorts and found no statistically significant increased risk after adjusting for cardiovascular risk factors (systolic blood pressure, LDL- and HDL-cholesterol, BMI, diabetes, and smoking).